Pemanfaatan Sampah Plastik sebagai Media Pengembangan Kreativitas Anak Jalanan di Kelurahan Tamangapa, Kecamatan Manggala, Kota Makassar - Andi Sadriani; Zainal Arifin; Muh. Nur; Firdaus W Suhaeb; Ernawati S Kaseng (PT Ininnawa Paramacitra Edu, 2026)
This community service activity aims to enhance the creativity of street children through the utilization of plastic waste as a medium for artistic creation in Tamangapa Subdistrict, Manggala District, Makassar City. The main problems faced by the participants include limited knowledge and skills in processing plastic waste, as well as a lack of awareness regarding its potential as a creative resource. The methods used in this activity include educational sessions, hands-on practice in creating collage artworks, and participatory evaluation. The results indicate an improvement in participants’ understanding of plastic waste management, increased skills in producing creative artworks, and positive changes in attitudes toward environmental awareness. In addition, the activity contributed to increased self-confidence and improved social interaction among participants. The use of plastic waste as a creative medium has proven effective in fostering contextual and meaningful learning experiences for street children. Therefore, this activity not only provides educational benefits but also contributes to community empowerment through creativity and environmental awareness.